2016
DOI: 10.1177/0165025416664195
|View full text |Cite
|
Sign up to set email alerts
|

Relations of shyness–sensitivity and unsociability with adjustment in middle childhood and early adolescence in suburban Chinese children

Abstract: This study examined how shyness–sensitivity and unsociability were associated with social, school, and psychological adjustment in Chinese children and adolescents. Participants included 564 children (272 boys, Mage=9 years) and 462 adolescents (246 boys, Mage=13 years) in a suburban region in China. Data were obtained from peer assessments, sociometric nominations, teacher-ratings, self-reports, and school records. The results showed that relations of shyness and unsociability with adjustment differed in midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
77
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 28 publications
7
77
3
Order By: Relevance
“…In China, empirical findings regarding unsociability and adjustment have been consistent across social contexts [urban, suburban, rural; note that methodology (e.g., informant, measures) has been relatively homogenous]. Consistent with the theoretical expectation, peer‐reported unsociability has been associated with pervasive concurrent adjustment problems in Chinese children and adolescents (Ding et al, ; Liu et al, ; Liu, Chen, et al, ; Liu et al, ). In the social domain, peer‐reported unsociability has been associated with peer problems, such as low peer preference and high peer rejection and victimization.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In China, empirical findings regarding unsociability and adjustment have been consistent across social contexts [urban, suburban, rural; note that methodology (e.g., informant, measures) has been relatively homogenous]. Consistent with the theoretical expectation, peer‐reported unsociability has been associated with pervasive concurrent adjustment problems in Chinese children and adolescents (Ding et al, ; Liu et al, ; Liu, Chen, et al, ; Liu et al, ). In the social domain, peer‐reported unsociability has been associated with peer problems, such as low peer preference and high peer rejection and victimization.…”
Section: Introductionmentioning
confidence: 76%
“…Unsociability has received less attention than shyness in the literature, perhaps because unsociable behaviors historically have been considered relatively benign in Western culture (e.g., Coplan, Prakash, O'Neil, & Armer, ). In recent years, accumulating evidence has suggested that in non‐Western cultures, primarily in China, unsociability is associated with social and school maladjustment (e.g., Ding, Weeks, Liu, Sang, & Zhou, ; Liu et al, ). Researchers have often attributed the inconsistent findings to cultural differences, arguing that unsociability may be considered more unacceptable in collectivistic cultures emphasizing group affiliation than in individualistic cultures emphasizing independence (Chen, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, shy children with high collectivistic values and low individualistic values may have better adjustment outcomes because they may view their shyness positively through the lens of cultural values. Although some studies have revealed cross‐country or ‐region differences suggesting collectivistic and individualistic cultural values may impact shy children’s adjustment (e.g., Chen, Wang, & Wang, ; Liu et al, ), no researcher has investigated directly the process of how individualistic and collectivistic cultural values influence shy children’s adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned findings suggest positive self‐ and other‐evaluation (evaluating behavior as appropriate through the lens of cultural values) in social and academic domains may be especially salient for shy Chinese adolescents’ adjustment. Firstly, shyness in China has been associated with more negative outcomes during adolescence than childhood, perhaps because assertiveness and individuality are highly valued in adolescence (Liu et al, ). Because adolescence is a period for identity development characterized by differentiating actual and ideal selves and self‐acceptance (Côté, ), self‐evaluation through the lens of cultural values may be especially crucial for shy adolescents’ adjustment.…”
Section: Introductionmentioning
confidence: 99%